Malaysia’s Changing Federal-State Relations – Kelantan & the PH Government - Najwa Abdullah (2019)
The Parti Islam se-Malaysia (PAS) state government in Kelantan had had difficult relationships with Barisan Nasional (BN) governments in Kuala Lumpur for as long as BN was in power. Will this change under the new Pakatan Harapan (PH) government?